The Development of an Assessment Framework for Elementary School Children in Higher Education Contexts - Chamisah (JURNAL ILMIAH MAHASISWA, 2024)
Evaluation This study explores the development of an assessment framework for elementary school children, informed by innovations and expertise from higher education contexts. Using a comprehensive library research methodology, it synthesizes insights from academic literature, theoretical frameworks, and existing assessment models. The proposed framework emphasizes a balanced integration of cognitive and socio-emotional dimensions to provide a holistic evaluation of student development. Key findings highlight the pivotal role of higher education institutions in designing robust, context-sensitive assessment tools that address diverse educational needs and align with developmental benchmarks.The study further underscores the importance of collaborative partnerships between higher education institutions and elementary schools to ensure the frameworks' relevance and applicability. Practical implications include the necessity for teacher training, policy alignment, and strategic resource allocation to support the adoption of these innovative frameworks. Additionally, the discussion explores future directions, such as incorporating artificial intelligence and adaptive technologies to enhance assessment practices. This research contributes to the growing discourse on educational assessment by proposing a transformative approach that aligns elementary school evaluations with contemporary educational goals and the demands of the 21st centur.